"A lot to fall back on": experiences of dyspareunia among queer women. Issue 5 (5th December 2022) - Ekholm, Elin; Lundberg, Tove; Carlsson, Jan; Norberg, Joakim; Linton, Steven J.; Flink, Ida K.
ABSTRACT: This study explores the subjective experiences of dyspareunia among queer women in Sweden. Ten semi-structured, in-depth interviews were conducted with five participants who were all interviewed on two separate occasions. Interviews were analysed using thematic analysis. Dyspareunia was described as affecting the participants' sexual activities, intimate relationships, and identity constructs. Reported struggles involved feelings of sadness, guilt, frustration, and fear of pain. Dyspareunia was described as threatening the participants' queer identities through its effect on their ability to be sexual in idealised ways. However, queer experiences and communities were also found to be associated with advantages in pain management, such as well-developed sexual communication skills, anatomic similarity to their partner, access to non-heteronormative sexual scripts and a focus on nurturing desire. Queer related advantages in pain management are proposed to buffer to some extent against pain interference with sexual function and desire. Findings indicate that it is important to consider the unique relational and social context of queer women to understand their experiences of dyspareunia. More research is needed on the role of differences of normativities, context and communication in dyspareunia.